Effect of chain‐extender modification on the structure and properties of thermoplastic poly(ether ester) elastomers. Issue 7 (5th October 2015) - John, Johnson V.; Kim, Kang Ryul; Baek, Seung Tae; Yoon, Ju Ho; Suh, Hongsuk; Kim, Il
ABSTRACT: The effect of the modulation of a bulky chain extender (CE), 4, 8‐bis(hydroxymethyl)tricyclo[5.2.1.0(2, 6)]decane (TCDO) or hydroquinone bis(hydroxyethyl)ether (HBHEE), on the properties of poly(ether ester) elastomers was investigated. The incorporation of various amounts of TCDO or HBHEE greatly changed the hard‐segment (HS) structure and microphase separation behavior; this resulted in a variation of the physical properties, especially for samples with high HS compositions. TCDO and HBHEE were used as minor CEs together with 1, 4‐butanediol as the major CE for the synthesis of poly(ether ester) elastomers based on the transesterification of dimethyl 2, 6‐naphthalene dicarboxylate with poly(tetramethylene ether glycol). On the basis of the amount of the minor CE incorporated, samples ranging from an elastomer to thermoplastic. The prepared samples were characterized by various spectroscopic, thermal, and mechanical analyses. The poly(ether ester) elastomers formed honeycomb‐structured porous films and microfibers (0.3–1.3 μm in diameter) through the application of a breath figures technique and electrospinning, respectively. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42888. Abstract :